Perspectivas de los estudios de arqueomagnetismo en Sudamérica - Greco Mainero, Mariano Catriel (2014)
Archaeomagnetism is the study of past geomagnetic field variations using bricks, pottery and campfire stones. This is a multidisciplinary work in which archaeologists, historians and geophysicists play important roles. For geophysicists, it contributes to the reconstruction and the study of local and global variations of the geomagnetic field, and it can serve as a dating tool for historical studies. However, this technique goes far beyond the chronological application, as it may provide information for paleoenvironmental studies and the provenance of objects. These studies are well developed in Europe, where there are records since the Middle Ages and a wide variety of recent data; on the contrary, data are scarce in the Southern Hemisphere, although several collaborative initiatives have enabled to make significant progress in recent years.